PHILOSOPHICAL FEATURES OF THE CULTURE OF MODERN - Клешня, Г. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article outlines the dominant philosophical Modern day in retrospect philosophical thought of Western civilization.